The Role of Stakeholders in Partnerships and Community Empowerment Against HIV/AIDS In Ternate City - Aja, Nursia; Tri Kartono, Drajat (CV. Inara, 2022)
The Non-Governmental Organization (NGO) Rorano was established to respond to the high number of morbidity and mortality due to the HIV and AIDS virus which continues to increase every year in North Maluku. In addition, the lack of public knowledge about the spread of HIV and AIDS is also not a concern for many people in North Maluku. Starting and thinking about simplicity, the NGO Rorano wants to build public awareness and joint partnerships in Ternate City to break the chain of HIV and AIDS transmission and eliminate community stigma and discrimination as well as solve the phenomenon of the iceberg in the case of HIV and AIDS. The type of community empowerment carried out by the role of stakeholders in partnerships and community empowerment for HIV and AIDS prevention is carried out for 6 days and is divided into several stages of implementing activities, especially in the health sector, especially in HIV and AIDS in the City of Ternate, namely: counseling, making billboards and installing billboards, leaflets containing information about HIV and AIDS prevention, and as a medium of socialization to prevent HIV and AIDS transmission in the community as well as family members or their children. The results of the activities of the NGO Rorano in collaboration with the government of Ternate City, as well as contributing to stakeholders in partnerships and community empowerment with HIV and AIDS prevention. Based on the results of the socialization in community empowerment activities that have been stated, the researchers draw conclusions from the results of the analysis that are as follows: there is a need for collaboration between the government and Chasan Boesoerie Hospital, City Health Office, 11 Puskesmas and involving all stakeholders in Ternate City, especially in handling holders of infectious disease programs so that they can control family members to prevent the transmission of HIV and AIDS in the City of Ternate